Composition of Powders Produced by Electrospark Dispersion of Metal Granules in Water; IOP Conference Series: Materials Science and Engineering; Vol. 110 : Radiation-Thermal Effects and Processes in Inorganic Materials (RTEP2015) - Zhuravkov S. P. Sergey Petrovich; Lobanova G. L. Galina Leonidovna; Pustovalov A. V. Aleksey Vitalievich; Slyadnikov P. E.; Nadeina L. V. Louise Vasilievna (2016, 2016)
Title screen